Analysis Of JHA, JSA and Management K3 At KIP 16 Bangka Ocean Mining Units PT Timah (Persero) Tbk Province Bangka Belitung Islands - Riri Rahmahwati Joni; Rusli HAR; Heri Prabowo (Journals Mining Engineering : Bina Tambang, 2018)
This research discuss about safety and health occupational control inBangka Ocean KIP Timah 16 Units using some risk management methodes. Themethodes are Job Hazard Analysis (JHA), Job Safety Analysis (JSA), and HazardIdentification Risk Assesment Determining Control (HIRADC). Purpose of theresearch is to explain safety and health occupational in KIP Timah 16 Unit it isfor get the improvement of productivity work, production, welfare andcomfortability workers and achievment of zero accident.The type pf the research is descriptive. There are two data had collected.They are primary and secondery data. Primary data get from interview with theemployees and secondary data get from K3 documents in thecenter company ofPT. Timah UPLB and KIP 16.Based on result of research can get some conclutions. First, explain safetyand health occupational system. Second, the implementation formula of FR, SRand IR to count total accident that lost from day work, percentage of accident fora month. Third, to use methode JHA, JSA and HIRADC for identification andcontrol occupational accident. And last, to arrange new SOP from analysis resultJHA, JSA, HIRADC and earlier SOP.